"DID I ASK FOR YOUR ADVICE?": EFFECTS OF ADVICE FROM PARENTS ON ADULT CHILDREN'S DEPRESSIVE SYMPTOMS. (20th December 2022) - Suitor, J Jill; Gilligan, Megan; Frase, Robert; Stepniak, Catherine
Abstract: Studies of intergenerational relations typically conceptualize advice as a positive dimension of exchanges between parents and adult children. In contrast, we suggest that advice may often be a source of interpersonal stress and thus have detrimental effects on psychological well-being. Further, we suggest that these effects vary by race and gender. To address these questions, we use data from 725 adult children regarding advice from mothers, collected as part of the Within-Family Differences Study. Multilevel regression analyses revealed that the impact of receiving advice varied by the combination of gender and race. Among sons, receiving advice predicted higher depressive symptoms, regardless of race. However, receiving advice predicted depressive symptoms among Black but not White daughters. Taken together, these findings question whether advice is a positive dimension of intergenerational interaction and suggest that mothers' advice may have a negative impact on adult children's depressive symptoms, particularly for sons and Black daughters.